Review of the Fund's Financing Role in Member Countries. (Policy Papers; Policy Paper ;, 2008)
This paper raises and discusses issues related to how the Fund provides financial assistance to its members. It is part of the strategic review to ensure the Fund remains relevant and effective. The objective is not to increase Fund lending, but to make sure the Fund has the right instruments and policies to help all of its members-with appropriate protection of Fund resources-as they integrate into a world of growing and increasingly complex cross-border flows. Other institutions (including major central banks and the World Bank) also are retooling their lending instruments and in the process grappling with similar issues. The paper offers a high-level view of the issues and does not make specific policy proposals. Policy proposals will be presented in follow-up papers, some of which are planned for Board discussion later in 2008.